The city’s internal boundaries in the light of socio-territorial realities. - Stébé, Jean-Marc; Marchal, Hervé (Springer VS, 2020)
This paper underlines the fact that the construction of political and administrative boundaries does not necessarily reflect the socio-economic realities and mental representations of urban dwellers living in different urban territories. Hence the importance of making a clear distinction, following Robert Escallier, between "imposed boundaries", which are the result of public policies, "spontaneous boundaries" deriving from segregation processes and "imaginary boundaries" based on social representations and mental images. Once made, these distinctions reveal the complexity of boundaries within ever-more fragmented metropolises and make it possible to detect the formation of real urban fragments, synonymous with strong social and territorial separatist dynamics. Yet, parallel to these developments, new centralities are emerging in urban peripheries, which calls into question the center-periphery model which has often been used by the media and by many political actors to describe the evolutions of contemporary cities. Further analysis can then shed light on the way in which, within peri-urban rings, socio-territorial fragmentation is developing, leading to the creation of boundaries between the historic and affluent peri-urban area located close to the city and the more distant peri-urban space, mostly inhabited by lower-income populations.
Keywords: Grenze; Stadt; Sozialstruktur; Peripherie; Stadtrand